2015
DOI: 10.1111/2047-3095.12086
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness and Efficiency of Nursing Care Documentation Using the SIMPRO Model

Abstract: SIMPRO meningkatkan kualitas dan fungsi sistem dukungan dalam memberikan asuhan keperawatan dan manajemen keperawatan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 31 publications
3
22
0
4
Order By: Relevance
“…Documentation will provide an accurate overview of clients, what happened and when it happened. The completeness in documentation is legal aspect proof of a nursing activity (2). Legal aspect showed the responsibility and nurse's accountability in their profession.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Documentation will provide an accurate overview of clients, what happened and when it happened. The completeness in documentation is legal aspect proof of a nursing activity (2). Legal aspect showed the responsibility and nurse's accountability in their profession.…”
Section: Introductionmentioning
confidence: 97%
“…Nursing care documentation can be done manually (paper-based) and also computerized (computer-based). The computerized system will help complete the generated documentation showed that the use of an integrated nursing information system could improve the quality of nursing documentation regarding comprehensiveness, relevance, decision-making functions, and legal aspects (2,6). Another study by Dwisatyadini et al showed a mean value of documentation completeness on "X" Hospital was 1.63 (40.75%) of the total value (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nursing care must be transparently described due to financial, legal (Health Insurance Act—KVG, 2016) and professional requirements (Müller‐Staub, Abt, Brenner, & Hofer, ). This can be achieved by applying and documenting the nursing process with standardized nursing languages (SNLs) (Escalada‐Hernández et al, ; Estrada & Dunn, ; Hariyati, Yani, Eryando, Hasibuan, & Milanti, ; Jones, Lunney, Keenan, & Moorhead, ; Pérez Rivas et al, ). This approach increases patient safety and leads to better nursing‐sensitive outcomes (Pérez Rivas et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by Hariyati et al (2011) show that there is a need of an integrated nursing management information system (NMIS) to enhance better coordination and collaboration between the Puskesmas, hospital and other related sector to provide better health care services (R. T. S. Hariyati, Delimayanti, & Widyatuti, 2011). Not only for management system but also can be used as education media for disharge planning and as nursing care documentation resulted on enhancement of documentation quality and time efficiency (R. T. S. Hariyati, Afifah, & Handiyani, 2010; R. T. S. H. Hariyati, Yani, Eryando, Hasibuan, & Milanti, 2016). A qualitative study on nurses focus group discussion show that they expect good development of telehealth or mobile health to support both patient and nurse (R. T. S. Hariyati & Sahar, 2012).…”
Section: Introductionmentioning
confidence: 99%